Enhancing Vocabulary Intervention for Kindergarten Students: Strategic Integration of Semantically Related and Embedded Word Review - Zipoli, Richard P.; Coyne, Michael D.; McCoach, D. Betsy (Remedial and Special Education, 2011)
Two approaches to systematic word review were integrated into an 18-week program of extended vocabulary instruction with kindergarten students from three high-need urban schools. Words in the embedded and semantically related review conditions received systematic and distributed review. In the embedded review condition, brief word definitions were integrated into the narratives of multiple storybooks. In the semantically related review condition, in-depth word review with explicit emphasis on semantic features and associations was provided during extension activities. Systematic review resulted in an almost twofold increase in target word learning. Embedded review was effective and time efficient, whereas semantically related review was time intensive but resulted in higher levels of word learning. There was a significant gain in Peabody Picture Vocabulary Test—III standard scores following the intervention.
Keywords: dept.cmd; peer-reviewed

Initiating Safe Oral Feeding in Critically Ill Intensive Care and Step-Down Unit Patients Based on Passing a 3-Ounce (90 Milliliters) Water Swallow Challenge - Leder, Steven B.; Suiter, Debra M.; Warner, Heather L.; Kaplan, Lewis J. (Journal of Trauma and Acute Care Surgery, 2011)
Background: Pulmonary aspiration is a leading cause of nosocomial infection in the intensive care unit (ICU) and step-down unit (SDU). A key goal is to identify patients who exhibit increased aspiration risk before beginning oral alimentation. This study investigated the success of recommending specific oral diets to ICU and SDU patients based on passing a 3-oz water swallow challenge. Methods: A referral-based sample of 401 ICU and 92 SDU patients were prospectively analyzed. Amount of liquid and food ingested at the next day's meal 12 hours to 24 hours after passing a 3-oz challenge and specific diet recommendations were accessed electronically from oral intake information entered on each participant's daily care sheets. Drinking and eating success, clinically evident aspiration events, and accuracy of diet order recommendations were recorded. Care providers were blinded to the purpose of the study. Results: All 401 ICU and 92 SDU patients were successfully drinking thin liquids and eating 12 hours to 24 hours after passing a 3-oz challenge. Mean volume of liquid ingested at the next day's meal was 360 mL ± 181.2 mL for ICU and 356.4 mL ± 173.5 mL for SDU patients. Percent of meal eaten ranged from 10% to 100%. Patient care sheets indicated specific diet recommendations were followed with 100% accuracy. Conclusions: Successfully recommending specific oral diets for ICU and SDU patients based on passing a 3-oz water swallow challenge was supported. Importantly, when a simple bedside 3-oz challenge administered by a trained provider is passed, specific diet recommendations can be made safely and confidently without the need for further objective dysphagia testing.
Keywords: dept.cmd; peer-reviewed

Effect of Presence/Absence of a Nasogastric Tube in the Same Person on Incidence of Aspiration - Fattal, Michael; Suiter, Debra M.; Warner, Heather L.; Leder, Steven B. (Otolaryngology–Head and Neck Surgery, 2011)
Objective. To determine what effect, if any, the presence or absence of a nasogastric (NG) tube in the same person had on the incidence of anterograde aspiration. Design. Case series with planned data collection. Setting. Large, urban, tertiary care teaching hospital. Subjects and Methods. Referred sample of 62 consecutively enrolled adult inpatients for fiber-optic endoscopic evaluation of swallowing (FEES). Group 1 (n = 21) had either small-bore (n = 13) or large-bore (n = 8) NG tubes already in place and had a FEES first with the NG tube in place and a second FEES after NG tube removal. Group 2 (n = 41) did not have an NG tube and had a FEES first without an NG tube and a second FEES after placement of a small-bore NG tube. Time between FEES was approximately 5 minutes. Patients were tested with thin liquid and puree food consistencies. Occurrence of aspiration for each consistency dependent on the presence or absence of an NG tube was recorded. Results. There were no significant differences (P > .05) in aspiration status for both liquid and puree consistencies in the same person dependent on presence or absence of either a small-bore or large-bore NG tube. Conclusions. Since objective swallowing evaluation (eg, FEES) can be performed with an NG tube in place, it is not necessary to remove an NG tube to evaluate for aspiration. Similarly, there is no contraindication to leaving an NG tube in place to supplement oral alimentation until nutritional requirements are achieved.
Keywords: dept.cmd; peer-reviewed

Multimodal communication training in aphasia: A pilot study - Purdy, M.; Van Dyke, J.A. (Journal of Medical Speech-Language Pathology, 2011)
Management of patients with aphasia often focuses on training nonverbal augmentative communication strategies; however, these strategies frequently do not generalize to natural situations. The limited success may be because training was not sufficient to produce an integrated multimodal semantic representation. The purpose of this study was to examine whether simultaneous training of stimuli in both verbal and nonverbal modalities would solidify the links within the semantic network and improve switching among modalities as needed in conversation. Two individuals with severe aphasia participated in 6 to 8 hours of Multimodal Communication Training (MCT), during which they conveyed a concept by verbalizing, gesturing, writing, and drawing. After practice with all modalities for a single concept, a new concept was introduced. Results showed that one participant increased conveyance of concepts on the functional communication task using a variety of modalities. Although some improvement was seen with the second participant, his overall performance remained poor, likely because of a greater impairment in semantic knowledge. After a brief period of semantic training, the second participant demonstrated additional gains. Thus, MCT may serve to increase switching among verbal and nonverbal modalities in individuals with intact semantic representations, thereby increasing the likelihood that individuals will use an alternative method to communicate. Copyright © 2011 Delmar Cengage Learning.
Keywords: AAC; Aphasia; Cognition; Multimodality; Treatment; adult; aged; article; ataxic aphasia; case report; communication skill; concept formation; cortical sensory aphasia; dept.cmd; disease severity; drawing; gesture; human; male; multimodal communication training; priority journal; semantic memory; task performance; verbalization; writing; ⛔ No DOI found

Comparison of reading performance in fluent and non-fluent aphasia - Purely, M.; Newman, D. (Procedia - Social and Behavioral Sciences, 2011)
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Procedia Soc. Behav. Sci.
Keywords: dept.cmd

Searching for Potocki–Lupski syndrome phenotype: A patient with language impairment and no autism - Ercan-Sencicek, A. Gulhan; Wright, Nicole R. Davis; Frost, Stephen J.; Fulbright, Robert K.; Felsenfeld, Susan; Hart, Lesley; Landi, Nicole; Mencl, W. Einar; Sanders, Stephan J.; Pugh, Kenneth R.; State, Matthew W.; Grigorenko, Elena L. (Brain & Development, 2011)
Potocki-Lupski syndrome (PTLS; OMIM 610883) is a genomic syndrome that arises as a result of a duplication of 17p11.2. Although numerous cases of individuals with PTLS have been presented in the literature, its behavioral characterization is still ambiguous. We present a male child with a de novo dup(17)(p11.2p11.2) and he does not possess any autistic features, but is characterized by severe speech and language impairment. In the context of the analyses of this patient and other cases of PTLS, we argue that the central feature of the syndrome appears to be related to diminished speech and language capacity, rather than the specific social deficits central to autism. © 2011.
10 citations (Crossref) [2023-10-31] Citation Key Alias: pop00090 tex.type: [object Object]
Keywords: 17p11.2; Autistic Disorder; Child; Chromosomes; Human; Pair 17; Humans; Inv(8)(q21.3-q24.1); Language Disorders; Language and speech impairment; Male; Phenotype; Potocki Lupski syndrome; Potocki-Lupski syndrome; Smith-Magenis Syndrome; academic achievement; adaptive behavior; article; case report; child; child development; chromosome 17p; chromosome duplication; clinical feature; dept.cmd; functional magnetic resonance imaging; genetic disorder; human; intelligence; language development; language disability; male; malformation syndrome; school child

Does the post-adoption environment significantly improve the verbal performance of young Russian adoptees - Felsenfeld, Susan; Hart, Lesley; Grigorenko, Elena (Behavior Genetics, 2011)
tex.organization: Behav Genet Assoc tex.researcherid-numbers: Grigorenko, Elena/V-2418-2019 tex.unique-id: ISI:000295326600062 41st Annual Meeting of the Behaviour-Genetics-Association, Newport, RI, JUN 06-09, 2011
Keywords: dept.cmd; ⛔ No DOI found

Phonetic variability in residual speech sound disorders exploration of subtypes - Preston, Jonathan L.; Koenig, Laura L. (Topics in Language Disorders, 2011)
Purpose: To explore whether subgroups of children with residual speech sound disorders (R-SSDs) can be identified through multiple measures of token-to-token phonetic variability (changes in one spoken production to the next). Method: Children with R-SSDs were recorded during a rapid multisyllabic picture naming task and an oral diadochokinetic task. Transcription-based and acoustic measures of token-to-token variability were derived. Articulation accuracy and general indices of language skills were measured as well. Results: Low correlations were observed between transcription-based and acoustic measures of phonetic variability, and among the acoustic measures themselves. Children who were the most variable on one measure were not necessarily highly variable on other measures. Transcription-based measures of variability were associated with language skills. Conclusions: Measures of phonetic variability did not identify children in the sample as consistently high or low. Data do not support the notion that clear subgroups based on phonetic variability can be reliably identified in children with R-SSDs. The link between highly variable phonetic output (quantified by transcription-based measures) and lower language skills requires further exploration.
18 citations (Crossref) [2023-10-31] tex.orcid-numbers: Preston, Jonathan/0000-0001-9971-6321 tex.researcherid-numbers: Preston, Jonathan/E-9310-2010 tex.unique-id: ISI:000290432200007
Keywords: acoustic analysis; dept.cmd; phonetic variability; residual speech sound disorders

Identifying residual speech sound disorders in bilingual children: A japanese-english case study - Preston, Jonathan L.; Seki, Ayumi (American Journal of Speech-language Pathology, 2011)
Purpose: To describe (a) the assessment of residual speech sound disorders (SSDs) in bilinguals by distinguishing speech patterns associated with second language acquisition from patterns associated with misarticulations and (b) how assessment of domains such as speech motor control and phonological awareness can provide a more complete understanding of SSDs in bilinguals. Method: A review of Japanese phonology is provided to offer a context for understanding the transfer of Japanese to English productions. A case study of an 11-year-old is presented, demonstrating parallel speech assessments in English and Japanese. Speech motor and phonological awareness tasks were conducted in both languages. Results: Several patterns were observed in the participant's English that could be plausibly explained by the influence of Japanese phonology. However, errors indicating a residual SSD were observed in both Japanese and English. A speech motor assessment suggested possible speech motor control problems, and phonological awareness was judged to be within the typical range of performance in both languages. Conclusion: Understanding the phonological characteristics of the native language can help clinicians recognize speech patterns in the second language associated with transfer. Once these differences are understood, patterns associated with a residual SSD can be identified. Supplementing a relational speech analysis with measures of speech motor control and phonological awareness can provide a more comprehensive understanding of a client's strengths and needs.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/109-148-393-297-363 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Articulation; Assessment; Bilingualism; Residual speech sound disorders; Speech motor control; dept.cmd

Change in pragmatic language in infant-toddlers with autism spectrum disorder: A retrospective study - Buckingham, Mallory; Newman, Diana B (Perspectives on Language Learning and Education, 2011)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/019-758-469-705-323 tex.type: [object Object]
Keywords: dept.cmd